REKOGNISI NEGARA TERHADAP PENDIDIKAN PESANTREN PASCA UNDANG-UNDANG NOMOR 18 TAHUN 2019: STUDI TENTANG IMPLIKASI TERHADAP KESETARAAN PENDIDIKAN ISLAM - Agus Hidayatullah; Kosasih; Ahmad Qurtubi; Ali Muhtarom (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to analyze the state's recognition of Islamic boarding schools (pesantren) following the enactment of Law No. 18 of 2019 concerning Islamic Boarding Schools and examine its implications for equality in Islamic education in Indonesia. As the oldest and most distinctive (traditional) Islamic educational institutions, Islamic boarding schools have historically received less equal recognition than other formal educational pathways. The enactment of Law No. 18 of 2019 marks a significant milestone in this recognition effort. This study uses a qualitative approach with library research methods to analyze relevant legal documents, policies, and academic literature. The analysis focuses on key articles in the Pesantren Law that regulate institutional recognition, graduate equality, and funding affirmation. The results indicate that Law No. 18 of 2019 provides strong formal legal recognition to Islamic boarding schools, placing them on par with other national educational pathways. The main implication is the realization of equality in Islamic education through: (1) Recognition of Graduate Diplomas/Syahadah Certificates, which enable Islamic boarding school alumni to continue on to higher education and access employment opportunities equivalent to graduates of public schools; (2) Strengthening the governance and education system of Islamic boarding schools, including recognition of the unique Islamic boarding school curriculum (Tafaqquh fiddin); and (3) Provision of facilitation and affirmation from the state, such as budget support, which was previously a major obstacle. However, the implementation of this law also leaves challenges, particularly related to the harmonization of technical policies at the regional level and maintaining the independence and uniqueness of Islamic boarding schools from potential excessive government intervention. This study concludes that state recognition through the Islamic Boarding School Law is a progressive step towards full integration and equality for Islamic education in Indonesia.